Fertility and family planning in Uttar Pradesh, India: major progress and persistent gaps - Shiva S. Halli; Damaraju Ashwini; Bidyadhar Dehury; Shajy Isac; Antony Joseph; Preeti Anand; Vikas Gothalwal; Ravi Prakash; B. M. Ramesh; James Blanchard; Ties Boerma (BMC, 2019)
Abstract Background Uttar Pradesh (UP) is the most populous state in India with historically high levels of fertility rates than the national average. Though fertility levels in UP declined considerably in recent decades, the current level is well above the government's target of 2.1. Data and methods Fertility and family planning data obtained from the different rounds of Sample Registration System (SRS) and the National Family Health Survey (NFHS). We analyzed fertility and family planning trends in India and UP, including differences in methods mix, using SRS (1971-2016) and NFHS (1992-2016). Bivariate and multivariate regression analyses were used. Results From 2000, while the total fertility rate (TFR) declined in UP, it is still well above the national level in 2015-16 (2.7 vs 2.18, respectively). The demand for family planning satisfied increased from 52 to 72% during 1998-99 to 2015-16 in UP, compared to an increase from 75 to 81% in India. Traditional methods play a much greater role in UP than in India (22 and 9% of the demand satisfied respectively), while use of sterilization was relatively low in UP when compared to the national averages (18.0 and 36.3% of current married women 15-49 years in UP and India, respectively in 2015-16). Within UP, district fertility ranged from 1.6 to 4.4, with higher fertility concentrated in districts with low female schooling, predominantly located in north-central UP. Fertility declines were largest in districts with high fertility in the late nineties (B = 7.33, p < .001). Among currently married women, use of traditional methods increased and accounted for almost one-third of users in 2015-16. Use of sterilization declined but remained the primary method (ranging from 33 to 41% of users in high and low fertility districts respectively) while condom use increased from 17 and 16% in 1998-99 to 23 and 25% in 2015-16 in low and high fertility districts respectively. Conclusions and implications Greater reliance on traditional methods and condoms coupled with relatively low demand for modern contraception suggest inadequate access to modern contraceptives, especially in district with high fertility rates. Family planning activities need to be appropriately scaled according to need and geography to ensure the achievement of state-level improvements in family planning programs and fertility outcomes.